Wielka ksiega polskich bajek - Golebiowski, Artur; Jucewicz, Andrzej (Warszawa : "Spar", 1993)
A collection of Polish fairy tales by some famous Polish authors for children ages 6 to 10.
Keywords: Tales -- Poland -- Juvenile literature; Children's stories, Polish; Children's poetry, Polish